Development of ultra wideband antenna array for human detection under debris - Ali, Jawad (2018)
Mega construction projects such as bridges and skyscapes are highly vulnerable to the natural disasters such as an earthquake, floods, and hurricanes. Any unfortunate accident may risk the life of residents living in such structures, the people might be trapped under the rubbles. Due to the reason, there is a requirement for efficient search and rescue systems to pull the victims out of the debris. Ground penetrating radar (GPR) plays an important role under in such circumstances to rescue the precious lives. In recent decades, the under-debris victim detection system using Doppler radar technique was developed and after that, the use of ultra-wideband (UWB) radar was also the part of a study for some years. However, the limitations in such systems are penetration depth and resolution imaging, and there is a need for such a system which addresses both while designing the single antenna. This research is about the designing of an antenna and its array that will be able to operate in entire UWB band defined from 3.1 GHz to 10.6 GHz, which is available freely for research and experimentation purpose. The reason for designing UWB antenna array is due to its ability to address penetration depth and high-resolution imaging of the detected object. Another purpose of designing an array is to achieve high gain and less power in order to nullify the adverse biological effects ofthe antenna. The designing of the antenna is the first task followed by the component testing and an experimentation setup to determine the detection capability. For the purpose, a new arc shape configuration is introduced in this research with the gain of around 6 dB and 13 GHz ofbandwidth. After the design simulation and fabrication, the experimentation was carried out using obstacles such as wood and concrete, and targeted human skin to validate the proposed detection scheme. The simulation and measurement results showed a good agreement in terms of detection depth and underground imagery. Thus it can be concluded from the results that the designed antenna array with nominal gain and bandwidth have the ability to detect behind the obstacle up to 0.66 m depth. Furthermore, these successful fabricated results of the design will be integrated with the radio frequency (RF) system as a part of future work to detect buried victims.